A produção e a circulação transnacional de livros em relevo para a educação de cegos (séculos XVIII-XIX) - Fulas, Tatiana de Andrade (2021)
The production of books with raised letters for the education of the blind began in France in 1784. Several alphabets were developed by inventors from different countries throughout the nineteenth century, inspired by the Roman alphabet and shorthand, being the Louis Braille code just one more among many others. This research aims to analyze who the inventors were, how they created their alphabets or codes, in what context they emerged, and which titles they printed and for whom. It intends to understand how the technology of the printing industry influenced the production of thousands of books distributed on a transnational scale, with the support of philanthropic societies and the state. The research sources are composed of conference proceedings, reports, biographies, autobiographies, photographs, periodicals, administrative memos, accounting records, catalogs, and correspondence collected in archives in the United States, England, Scotland, and France. According to transnational perspective and comparative history, this work analyzes the connection between actors from different geographic spaces who have established relationships beyond their border areas, revealing a global phenomenon of production, circulation, and consumption of textbooks for the education of the blind. The analysis methodology is centered on the paleography proposed by Armando Petrucci, considering the invention of alphabets as more than an ordered system of graphic signs, understood from the struggle of a minority to appropriate a medium of communication monopolized by power groups. The research reveals that the adoption of the Braille code went through a period of fierce disputes between inventors, at the same time as the assumptions for the education of the blind in regular schools emerged. The universalization and standardization of the Louis Braille code would take almost two centuries to implement worldwide, and its efficiency is quarrel until the 21st century